Production of Epoxyketone Peptide-Based Proteasome Inhibitors by Streptomyces sp. BRA-346: Regulation and Biosynthesis - Domingues Vieira, Bruna; Niero, Henrique; de Felício, Rafael; Giolo Alves, Luiz Fernando; Freitas Bazzano, Cristina; Sigrist, Renata; Costa Furtado, Luciana; Felix Persinoti, Gabriela; Veras Costa-Lotufo, Leticia; Barretto Barbosa Trivella, Daniela (Frontiers in Microbiology, 2022)
Streptomyces sp. BRA-346 is an Actinobacteria isolated from the Brazilian endemic tunicate Euherdmania sp. We have reported that this strain produces epoxyketone peptides, as dihydroeponemycin (DHE) and structurally related analogues. This cocktail of epoxyketone peptides inhibits the proteasome chymotrypsin-like activity and shows high cytotoxicity to glioma cells. However, low yields and poor reproducibility of epoxyketone peptides production by BRA-346 under laboratory cultivation have limited the isolation of epoxyketone peptides for additional studies. Here, we evaluated several cultivation methods using different culture media and chemical elicitors to increase the repertoire of peptide epoxyketone production by this bacterium. Furthermore, BRA-346 genome was sequenced, revealing its broad genetic potential, which is mostly hidden under laboratory conditions. By using specific growth conditions, we were able to evidence different classes of secondary metabolites produced by BRA-346. In addition, by combining genome mining with untargeted metabolomics, we could link the metabolites produced by BRA-346 to its genetic capacity and potential regulators. A single biosynthetic gene cluster (BGC) was related to the production of the target epoxyketone peptides by BRA-346. The candidate BGC displays conserved biosynthetic enzymes with the reported eponemycin (EPN) and TMC-86A (TMC) BGCs. The core of the putative epoxyketone peptide BGC (ORFs A-L), in which ORF A is a LuxR-like transcription factor, was cloned into a heterologous host. The recombinant organism was capable to produce TMC and EPN natural products, along with the biosynthetic intermediates DH-TMC and DHE, and additional congeners. A phylogenetic analysis of the epn/tmc BGC revealed related BGCs in public databases. Most of them carries a proteasome beta-subunit, however lacking an assigned specialized metabolite. The retrieved BGCs also display a diversity of regulatory genes and TTA codons, indicating tight regulation of this BGC at the transcription and translational levels. These results demonstrate the plasticity of the epn/tmc BGC of BRA-346 in producing epoxyketone peptides and the feasibility of their production in a heterologous host. This work also highlights the capacity of BRA-346 to tightly regulate its secondary metabolism and shed light on how to awake silent gene clusters of Streptomyces sp. BRA-346 to allow the production of pharmacologically important biosynthetic products.